Crossing the Threshold From Porn Use to Porn Problem: Frequency and Modality of Porn Use as Predictors of Sexually Coercive Behaviors - Marshall, Ethan A. (Journal of interpersonal violence, 2021)
According to recent statistics, as many as one in five female college students are victims of sexual assault during their college career. To combat what has been called the “Campus Rape Crisis,” researchers have attempted to understand what variables are associated with sexually coercive behaviors in college males. Although investigators have found support for the relationship between pornography consumption and sexually coercive behavior, researchers typically operationalize pornography use in terms of frequency of use. Furthermore, frequency of use has been assessed vaguely and inconsistently. The current study offered a more concrete assessment of frequency of use and an additional variable not yet included for pornography use: number of modalities. Beyond examining the relationship between pornography use and sexual coercion likelihood, the current study was the first to use pornography variables in a threshold analysis to test whether there is a cut point that is predictive of sexual coercion likelihood. Analyses were conducted with a sample of 463 college males. Results indicated that both pornography use variables were significantly related to a higher likelihood of sexually coercive behaviors. When both frequency of use and number of modalities were included in the model, modalities were significant and frequency was not. In addition, significant thresholds for both pornography variables that predicted sexual coercion likelihood were identified. These results imply that factors other than frequency of use, such as number of modalities, may be more important for the prediction of sexual coercive behaviors. Furthermore, threshold analyses revealed the most significant increase in risk occurred between one modality and two, indicating that it is not pornography use in general that is related to sexual coercion likelihood, but rather, specific aspects of pornography use.